Modulators of actin - King, Mary-Claire (1998)
The invention provides methods and compositions which find use, $i(inter alia), for modulating the stabilization of actin filaments. The compositions may comprise one or more polypeptide moieties derived from a novel human diaphanous polypeptide and/or one or more nucleic acid moieties derived from a novel human diaphanous gene or gene transcript. The invention also provides agents which specifically modify the binding of a natural human diaphanous gene or gene product with a natural binding target thereof, isolated human diaphanous hybridization probes and primers capable of specifically hybridizing with the disclosed human diaphanous genes, human diaphanous-specific binding agents such as specific antibodies, and methods of making and using the subject composition in diagnosis, therapy and in the biopharmaceutical industry.